3-D InISAR Imaging of the Ship Target Based on Joint Cross S-Method Algorithm - Wang, Yong; Chen, Xuefei (IEEE geoscience and remote sensing letters, 2019)
3-D interferometric inverse synthetic aperture radar (InISAR) imaging of ship targets has always been a hot and difficult issue in research, and how to preserve the interferometric phase while performing high-resolution 2-D ISAR imaging of the complex echoes is the key to 3-D InISAR imaging. In this letter, a novel 3-D InISAR imaging algorithm of the ship target based on joint cross S-method is proposed. First, the azimuth short-time Fourier transform (STFT) is applied to the 1-D range profiles after motion compensation and image coregistration. Then, extract the interferometric phase matrices after performing the joint cross S-method transformation of the STFT results along the two baselines. Besides, the S-method transformations are implemented recursively for the joint cross S-method transformed results to obtain high-resolution ISAR images. Finally, the 3-D InISAR imaging can be achieved by combining the phase matrices and ISAR images at the same time. Simulation results verify the effectiveness and superiority of the proposed algorithm.